Desvios de ortografia na escrita de alunos do sexto ano de uma escola estadual de Conceição das Alagoas, MG: proposta de intervenção - PAULA, Helenice Bento Fontes de (2020)
This dissertation, following the theoretical methodological perspective of Educational Sociolinguistics, aims to describe the motivations for the occurrence of orthographic deviations in the writing of sixth year Middle School students from a public school in the municipality of Conceição das Alagoas, in the interior of Minas Gerais, and, based on these results, present an intervention proposal (the production of a “Caderno Didático”/ Didactic Workbook). To achieve our goals, initially, in addition to the t heoretical review on the subj ect, we analyzed how the sixth year textbook used by the school’s teacher addresses the issue of orthographic deviations and linguistic variation. In addition, we performed: (i) the diagnosis and typification (BORTONI RICARDO, 2005; SENE, BARBOSA, 2018) of the orthographic deviations presented by the students in written textual productions; (ii) the application of a questionnaire to collect information about the social profile and some habits of the students and (iii) the elabor ation and application of a Didactic Workbook, based on the results of the orthographic deviation diagnosis as an intervention tool, with reflexive and dynamic didactic activities for teaching spelling, taking into account linguistic variation and language modalities (and the continuum between oral and written language). Such a workbook seeks to lead the student to appropriate his writing more effectively, respecting linguistic diversity. The Didactic Workbook presents a brief theoretical and didactic orient ation of some contents for the teacher and a proposal of activities in relation to the oral and writing modality, and also in relation to the orthographic deviations, according to the categorization of the deviation types. The guidelines for teachers make significant contributions to teaching the language in the most different social situations and the proposed activities for students show that continuous and systematic work is needed to develop, through the reflective and inductive method, understanding wi th inferences the rules to be followed starting from recurrences and putting them into practice in the construction of their own knowledge. This work also contemplates a discussion on orthographic deviations, their motivations, categorizations and activity proposals that help students to better understand the role of linguistic variety in their communicative competence in the most varied contexts. There are also some suggestions for reading references as support activities that contribute to the students’ e ducational practice and as a pedagogical intervention in Portuguese language classes.